PEMBUATAN PAKAN PELLET BERBASIS TEKNOLOGI INTEGRASI KAKAO-KAMBING DI DESA TINAMBUNG KECAMATAN PAMBOANG KABUPATEN MAJENE - Irmayanti, Irmayanti; Haloho, Ruth Dameria; Ilham, Ilham; Suyono, Suyono; Sarman, Aco Parawansa; Suardi, Suardi; Minanga, Yunus Tandi (Jurnal Abdi Insani, 2024)
The Farmers in Tinambung Village, Pamboang Subdistrict, Majene Regency mostly raise goats as a side job to support their income. Cocoa shells, which are cocoa plantation waste, have not been utilized so far, only as waste that pollutes the environment. The farmer-livestock group “Siparare” is a partner in community service activities totaling 35 people. This activity aims to provide education on the utilization of cocoa shells as animal feed and skills in making feed in the form of pellets. The methods used in this activity are survey, counseling, training, and monitoring and evaluation. Measurement of farmers' knowledge was done through pre-test and post-test. The results show that the knowledge and skills of farmers have increased significantly from 6.43% to 76.29% in processing cocoa shell waste into feed pellets as an alternative to fulfill quality feed needs, especially during the dry season. Pellets as an alternative in fulfilling the need for quality feed, especially during the dry season. Based on the results of observations during the activity, the results of questions and answers and the enthusiasm of the participants, it can be seen that new partners are aware of the existence of innovative feed processing technology and the importance of the role of feed as a source of nutrition for livestock, willingness to apply pellet feed processing technology, and enthusiasm in adopting the material provided, so overall this activity can be said to be quite successful. Farmers have been able to make feed pellets from cocoa shells independently as a solution in providing quality feed as well as a product with economic value so as to increase farmers' income, and can utilize and reduce waste that can pollute the environment.